Penerapan Teori Belajar Sibernetik dalam Upaya Meningkatkan Kreativitas Siswa di SD IT Assajidin Kab. Sukabumi - Siti Ulfah Fauziah; Mulyawan Safwandy Nugraha (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2023)
This research is a qualitative research using field research methods and literature review which aims to explore and analyze the contribution of the application of cybernetic learning theory in increasing student learning creativity in the subject of Islamic Religious Education (PAI) at Elementary School IT Assajidin, Sukabumi Regency. Cybernetic learning theory is an approach that sees learning as a system that is interconnected between existing elements, including students, teachers, the learning environment, and the interactions within it. This research involves a literature review process that focuses on studying cybernetic learning theory and its impact on increasing student learning creativity in the context of PAI subjects at SD IT Assajidin. Data and information were obtained through searches of related journals, scientific articles and other relevant literature. The results of the literature review show that the application of cybernetic learning theory has great potential in increasing student learning creativity in PAI subjects at SD IT Assajidin, Sukabumi Regency. The concept of interaction between learning elements in this theory is able to create an environment that stimulates the development of students' creativity through dialogue, reflection, and adaptation to their learning experiences. In addition, the observation results also reveal that the cybernetic approach can assist teachers in designing learning strategies that are more dynamic and flexible, so that they are able to overcome challenges that may arise in learning PAI subjects. Interactions centered on cybernetic learning can also encourage students to think critically, collaborate with others, and develop unique ways of understanding religious concepts. This study underscores the importance of applying cybernetic learning theory in the context of Islamic religious education at SD IT Assajidin, Sukabumi Regency. Nonetheless, further research is needed to investigate the concrete implementation of this theory in teaching PAI and the real impact it produces in increasing student learning creativity.